Network Analysis of RAD51 Proteins in Metazoa and the Evolutionary Relationships With Their Archaeal Homologs - Jiang, Shan; Lin, Ting; Xie, Qingji; Wang, Lijing (Frontiers in Genetics, 2018)
The RAD51 recombinases are essential for homologous recombination, DNA repair, and genome stability. Overexpression of RAD51 protein has been observed in many cancer cells, such as thyroid carcinoma, breast cancer, pancreatic cancer and others. In Metazoa, there are multiple members of RAD51 (RAD51, RAD51B, RAD51C, RAD51D, DMC1, XRCC2, and XRCC3). In this study, we used a protein sequence similarity network (SSN) to analyze the evolutionary relationship within this protein family. The SSN based on the RAD51 proteins from Metazoa indicate that there are plenty of proteins that have not been functionally defined. The SSN based on the distribution of the proteins supports the hypothesis that horizontal gene transfer plays an important role in the evolution. Multiple sequence alignments reveal that the amino acid residues for ATP and Mg2+ is highly conserved. The seven RAD51 proteins in human are under different selective pressure: RAD51 and DMC1 are under stringent negative selection while other proteins are subject to relatively relaxed negative selection. Furthermore, the expression values of the 7 genes in different tissues showed that the genes in the same cluster in phylogenetic tree showed similar expression profiles. Finally, the SSN based on the RAD51 proteins from both eukaryotes and prokaryotes suggested that the eukaryotic RAD51 recombinases share a common ancestor with the archaeal homologs but XRCC2 may have a different origin. These findings expand the understanding of the evolution and diversity of RAD51 recombinases in Metazoa.